2017
DOI: 10.1103/physreve.96.053102
|View full text |Cite
|
Sign up to set email alerts
|

Flow instabilities due to the interfacial formation of surfactant–fatty acid material in a Hele-Shaw cell

Abstract: We present an experimental study of pattern formation during the penetration of an aqueous surfactant solution into a liquid fatty acid in a Hele-Shaw cell. When a solution of the cationic surfactant cetylpyridinium chloride is injected into oleic acid, a wide variety of fingering patterns are observed as a function of surfactant concentration and flow rate, which are strikingly different than the classic Saffman-Taylor (ST) instability. We observe evidence of interfacial material forming between the two liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Aqueous surfactant solutions containing spherical micelles have been previously shown to develop various interfacial instabilities when the micelles come into contact with a second solution such as NaSal solution or fatty acid [48][49][50]. Here, we show that similar interfacial instabilities form when a CPCl solution is injected into OA.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Aqueous surfactant solutions containing spherical micelles have been previously shown to develop various interfacial instabilities when the micelles come into contact with a second solution such as NaSal solution or fatty acid [48][49][50]. Here, we show that similar interfacial instabilities form when a CPCl solution is injected into OA.…”
supporting
confidence: 51%
“…However, research on dynamic phenomena in which structural self-assembly stabilizes the interface under nonequilibrium conditions is still in its infancy. This is despite the fact that in situ self-association of amphiphilic molecules has been widely observed for a variety of practical or industrial applications including oil recovery [45][46][47], flow instabilities [20,[48][49][50][51], biological systems [52][53][54], and rare metal extraction [55]. There has yet to be a fundamental study on dynamics of interfacial material formation between associating surfactants at immiscible liquid interfaces, and the connection between structure and property relationships, in addition to the underlying mechanism of structure development at the molecular level.…”
mentioning
confidence: 99%
“…This instability has been thoroughly studied both experimentally and theoretically because, among others, of its ubiquity in oil recovery when a fluid like water or CO2 displaces the more viscous oil in the soils (Saffman & Taylor (1958), Homsy (1987)). In this context, reactions producing for instance surfactants in situ can modify the local surface tension and affect the Safmann-Taylor instability between two immiscible fluids (Jahoda & Hornof (2000), Nasr-El-Din et al (1990), Hornof & Baig (1995), Fernandez & Homsy (2003), Niroobakhsh et al (2017), Tsuzuki et al (2019)). We won't review this particular case as we focus here on miscible systems.…”
Section: Viscous Fingering In Reactive Systemsmentioning
confidence: 99%
“…When the flow rate increases, the interface becomes more unstable and the number of fingers increases. The fingers become narrower and side-branching occurs 3,4,5,8,14,20 .…”
Section: A Fingering Patterns For Newtonian and Non-newtonian Fluidsmentioning
confidence: 99%
“…Recently Tsuzuki et al 19 proposed an alternative explanation and suggested that surfactant advection could be enhanced by a combination of fountain flow and Marangoni effect 46 . Niroobakhsh et al 20,21 investigated the injection of cationic surfactant solution into oleic acid and included the interfacially forming material as a cause of the viscous instabilities.…”
Section: Introductionmentioning
confidence: 99%